Discovery of Chlorogenic Acid-Based Peptidomimetics as a Novel Class of Antifungals. A Success Story in Rational Drug Design - Mohsen Daneshtalab (Frontiers Media S.A., 2008)
Life-threatening fungal infections have increased dramatically in recent decades in immunocompromised patients. An estimated 40% of all deaths from hospital-acquired infections are due to infections caused by opportunistic fungi. The current treatment options are either causing serious toxicity, or becoming inactive against the drug-resistant fungal strains. Thus, the discovery and development of new antifungal agents that are economically feasible, have excellent therapeutic value, and address the problems of toxicity and species resistance is very important. We have recently designed and synthesized a series of chlorogenic acid-based peptidimimetics using structure-based methodology starting with cyclic peptides of the candin class of antifungals. These novel and totally synthetic compounds exhibit promising antifungal activity against pathogenic fungi with very low toxicity against brine shrimps. The possible novelty in their mechanism of action and economically feasible synthetic approach are the attractive features of this class of compounds that make them different from the already utilized antifungal agents.